Elevated Expression of Serum Amyloid A 3 Protects Colon Epithelium Against Acute Injury Through TLR2-Dependent Induction of Neutrophil IL-22 Expression in a Mouse Model of Colitis - Zhang, Gufang; Liu, Jin; Wu, Lehao; Fan, Yu; Sun, Lei; Qian, Feng; Chen, Daijie; Ye, Richard D. (Frontiers in Immunology, 2018)
Induced expression of serum amyloid A (SAA) is a hallmark of many inflammatory diseases, but whether SAA exacerbates inflammation or protects tissues against injury remains unclear. In dextran sulfate sodium (DSS)-induced colitis, SAA3 is the predominant isoform of inducible SAA proteins that also include SAA1 and SAA2, and mice with genetic deletion of Saa3 exhibits increased production of pro-inflammatory cytokines, decreased expression of IL-22 along with aggravated epithelium disruption and reduced colon length compared with wildtype littermates. Colonic neutrophils have been identified as a major source of IL-22 in these mice. Administration of exogenous SAA3 as recombinant protein to Saa3-/- mice improves neutrophil IL-22 production, colonic epithelial integrity and secretion of the anti-microbial peptides Reg3 and Reg3. Stimulation of mouse bone marrow neutrophils with mouse SAA3 or human SAA1 leads to expansion of IL-22-producing neutrophils. Unlike previously reported IL-22 induction through IL-23, the SAA3-induced neutrophil IL-22 expression utilizes a TLR2-dependent mechanism that does not depend on IL-23. Adoptive transfer of the SAA3-treated neutrophils to Saa3-/- mice ameliorates DSS-induced colitis and improves colonic epithelial integrity. These findings suggest that in the DSS-induced mouse colitis model, SAA isoforms are expressed to different extent in colon and deletion of Saa3 renders these mice more susceptible to DSS-induced injury. The presence of SAA3 in the inflamed colon mucosal serves to protect epithelial barrier in part through expansion of IL-22-producing neutrophils. It is speculated that SAA3 stimulation of autologous neutrophils may have therapeutic potential for inflammatory bowel disease.